(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The article examines the role of the trigeminal system in the pathogenesis of migraine, as well as the phenomenon of subjective premonition of attack onset. The prodromal period of migraine, its neurobiological mechanisms, and clinical significance are highlighted. The activation of the trigeminovascular system, central sensitization, and the involvement of the hypothalamus are analyzed. The significance of this phenomenon for early diagnosis and preventive therapy is substantiated.